2016
DOI: 10.3389/fpsyg.2016.01558
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Functional Brain Networks Underlying Temporal Integration of Audio-Visual Speech Perception: An EEG Study

Abstract: Observable lip movements of the speaker influence perception of auditory speech. A classical example of this influence is reported by listeners who perceive an illusory (cross-modal) speech sound (McGurk-effect) when presented with incongruent audio-visual (AV) speech stimuli. Recent neuroimaging studies of AV speech perception accentuate the role of frontal, parietal, and the integrative brain sites in the vicinity of the superior temporal sulcus (STS) for multisensory speech perception. However, if and how d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…Alpha and gamma band coherences are observed in processing of multisensory stimulus (Hummel & Gerloff, 2005; Kanayama et al, 2007; Doesburg et al 2008; Kayser et al, 2008; Maier et al, 2008; Kayser & Logothetis, 2009; Kumar et al, 2016; also present results, Figure 2 ). Interestingly, high gamma coherence is seen when the nature of multisensory stimulus is complex (asynchronous, incongruent) (Doesburg et al, 2008; Kumar et al, 2016 and present results, Figure 2 ) which in some instances lead to illusory perception (Kanayama et al, 2007; Kumar et al, 2016; and present results, Figure 1 ). Gamma coherence is also observed in the communication involving higher order multisensory areas (Maier et al, 2008; and present results, Figure 4 ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Alpha and gamma band coherences are observed in processing of multisensory stimulus (Hummel & Gerloff, 2005; Kanayama et al, 2007; Doesburg et al 2008; Kayser et al, 2008; Maier et al, 2008; Kayser & Logothetis, 2009; Kumar et al, 2016; also present results, Figure 2 ). Interestingly, high gamma coherence is seen when the nature of multisensory stimulus is complex (asynchronous, incongruent) (Doesburg et al, 2008; Kumar et al, 2016 and present results, Figure 2 ) which in some instances lead to illusory perception (Kanayama et al, 2007; Kumar et al, 2016; and present results, Figure 1 ). Gamma coherence is also observed in the communication involving higher order multisensory areas (Maier et al, 2008; and present results, Figure 4 ).…”
Section: Discussionsupporting
confidence: 72%
“…Hence, it is important to identify which of these are meaningful to the ongoing task and the subtle differences that vary with the context in which the task evolves. In an earlier study Kumar et al (Kumar et al, 2016) have showed that global coherogram captures the difference in processing of crossmodal (illusory / ta /) and unimodal (non-illusory / pa /) perception in frequent perceivers from a subset of data that we present in this manuscript. While the detailed pattern of coherogram differences between / ta / and / pa / trials in perceivers and rare perceivers are slightly different, there was an enormous similarity in trend of coherence differences in distinct spectro-temporal locations that was conspicuous.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Many studies have shown the relationship between the electrical activity of brain and complex psychophysiological processes such as alertness [1], arousal [2], attention [3], memory [4], and executive functions [5]. Among these tasks, analysis of brain activity related to processing of visual stimuli is one of the most interesting and actively studied in modern science [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…To measure the covariation of neural oscillations on a global level, we employed a technique known as global coherence (Cimenser et al, 2008;Kumar et al,2016). Global coherence among sensors at any frequency f is measured as the percentage of variance explained by the first eigenvector of the cross spectral density matrix at f .…”
mentioning
confidence: 99%